Implementation of Moral Values in Scouts (Study on Madrasah Ibtidaiyah State 1 Medan) - Haidir Haidir; Daisy JP; Evi Idayani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Implementation is a way or process of application carried out by students, after getting material or theory from educators then students realize what they learn through action. Education is a way that can change human behavior or mindset. While the moral is the nature, attitude, temperament or habits inherent in humans. While the scout movement is a form of integration that has been formed and regulated in Act Number 12 of 2010 concerning the Scout Movement. Hidden Curriculum is one of the strategies that proves that hidden curriculum can influence the learning process especially in instilling moral values. This research is a qualitative research with descriptive type. The informants in this study were the Trustees and Students of Madrasah Scout Ibtidaiyah Negeri 1 Medan. The results showed that the scouts of Madrasah Ibtidaiyah Negeri 1 Medan had implemented the moral values in the Scout Movement activities well. This is evidenced by a special program of moral education, scouting activities containing moral education, special programs containing moral values such as the implementation of social services or fundraising, then mutual cooperation conducted at school or outside school. However, the Boy Scouts at MIN 1 Medan continue to implement improvements in improving moral education and to realize students or scout members who are dharma-based and have Satya teachings.